The field-size effect: Short motions look faster than long ones. (May 2018) - Anstis, Stuart; Kim, Juno
Abstract: Reducing the amount of motion information can surprisingly make motion look faster (e.g., motion behind Venetian blinds). We found that a textured pattern moving to the right at speeds ranging from 0.34 to 5.5°/s appeared to move 50% faster when viewed through a short (0.5°) compared with a long (4.5°) horizontal slot. Perceived speed varied inversely with the log of the slot length. We varied the length of rectangular apertures over a tenfold range and manipulated their size, shape, and orientation. We attribute the field-size effect mostly to landmarks provided by the ends of the slots, but we also examined temporal and spatial frequency and lateral inhibition of motion.